A critical analysis of the political discourse of exceptionalism in the American Sniper movie - Akvani, Hamdallah (Array, 2020)
Political discourse usually tends to diffuse itself in other discursive fields. One of the areas through which the political field can be reproduced is the field of popular culture, especially films. Moreover, language serves as the intermediate variable in which political discourses in the media offer themselves more or less ideologically. In this paper, the language of the film American Sniper and its relation to the exceptionalism discourse in the politics of the United States is reviewed. It addresses the major question of how the discourse of American Sniper is related to the three layers of exceptionalism discourse. The analysis of the three discursive levels of description, interpretation and explanation of the film based on Fairclough’s model reveals that, by following Hollywood’s dominant framework of discourse towards Islam and the Middle East, i.e., the ‘Islamophobia’ discourse, the film depicts Islam as 'Other'. The discourse of the film ultimately resides in a wider social action that is congruous with the concept of the political language of exceptionalism.